Risk Analysis of Musculoskeletal Disorders Using RWL And LI Methods - Nuril Fahmi; Deny Andesta (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Material handling is an activity that is often carried out by everyone in daily activities, especially in activities in a company. Material transfer or material handling without the use of tools, commonly referred to as